Perceptions about cancer and barriers towards cancer screening among ethnic minority women in a deprived area in Denmark - a qualitative study - Camilla Rahr Tatari; Berit Andersen; Trine Brogaard; Sara Koed Badre-Esfahani; Negin Jaafar; Pia Kirkegaard (BMC, 2020)
Abstract Background Screening programmes for cervical cancer, breast cancer and colorectal cancer have been implemented in many Western countries to reduce cancer incidence and mortality. Ethnic minority women are less likely to participate in cancer screening than the majority population. In worst case this can result in higher incidence rates, later diagnosis and treatment and ultimately inferior survival. In this paper we explored the perceptions about cancer and perceived barriers towards cancer screening participation among ethnic minority women in a deprived area in Denmark. Methods Interview study with ethnic minority women in a deprived area in Denmark. The interviews were transcribed verbatim followed by an inductive content analysis. Results Cancer was perceived as a deadly disease that could not be treated. Cancer screening was perceived as only relevant if the women had symptoms. Knowledge about cancer screening was fragmented, often due to inadequate Danish language skills and there was a general mistrust in the Danish healthcare system due to perceived low medical competences in Danish doctors. There was, however, a very positive and curious attitude regarding information about the Danish cancer screening programmes and a want for more information. Conclusion Ethnic minority women did not have sufficient knowledge about cancer and the purpose of cancer screening. Perceptions about cancer screening were characterised by openness and the study showed positive and curious attitudes towards screening participation. The findings emphasise the importance of culturally adapted interventions for ethnic minority women in attempts to reduce inequality in screening participation.